2021
DOI: 10.3390/diagnostics11061121
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral CT Perfusion in Acute Stroke: The Effect of Lowering the Tube Load and Sampling Rate on the Reproducibility of Parametric Maps

Abstract: The aim of this study was to define lower dose parameters (tube load and temporal sampling) for CT perfusion that still preserve the diagnostic efficiency of the derived parametric maps. Ninety stroke CT examinations from four clinical sites with 1 s temporal sampling and a range of tube loads (mAs) (100–180) were studied. Realistic CT noise was retrospectively added to simulate a CT perfusion protocol, with a maximum reduction of 40% tube load (mAs) combined with increased sampling intervals (up to 3 s). Perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
(40 reference statements)
0
6
0
Order By: Relevance
“…Consequently, the definition of the lowest feasible sampling rate is an ongoing debate. There has been a prevailing notion that a temporal sampling below 2 s is required [ 10 , 12 , 13 ]. Some studies reported miscalculation of perfusion values and underestimation of ischemic volume when increasing the temporal sampling beyond this point [ 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the definition of the lowest feasible sampling rate is an ongoing debate. There has been a prevailing notion that a temporal sampling below 2 s is required [ 10 , 12 , 13 ]. Some studies reported miscalculation of perfusion values and underestimation of ischemic volume when increasing the temporal sampling beyond this point [ 7 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whereas previous studies on the concept of increased temporal sampling in CTP relied on rather small datasets [ 7 – 9 , 11 , 12 ], we examined a large dataset from a clinical routine which included a wide range of scan qualities. Here, we found that impaired data quality (for example due to motion, late contrast arrival, or low contrast to noise ratios) resulted in stronger artifacts when reducing the temporal resolution.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the protocol optimization stage, enhanced communication between different centres can lead to an overall quality improvement through optimization of radiation dose and contrast administration, higher patient safety and overall better diagnostic quality ( 35 , 36 ). Moreover, such enhanced communication can facilitate comparing the results obtained from different studies, thus reducing the variability due to different imaging protocols ( 37 , 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Computationally, TMSP is the time required for the first derivative of Equation (1) to reach its maximum value. These equations have been used to describe the dispersion of a bolus as it passes through a series of compartments, mainly for perfusion modeling [ 33 , 34 , 35 , 36 ]. Further information and graphical representation of the quantitative markers for EMG can be found in [ 37 , 38 ].…”
Section: Methodsmentioning
confidence: 99%